Political Mechanisms Of Decentralization In Public Administration: The Case Of South Korea - Safarov Islombek Shavkatovich (Genius Journals, 2025)
This study analyzes the political factors that have facilitated the decentralization of public administration in the Republic of Korea. Following its democratic transition in the late 1980s, Korea has steadily advanced in enhancing local self-governance and delegating administrative powers from the central government to local authorities. The research investigates the institutional, legal, administrative, and fiscal structures that have supported this transformation, highlighting their roles in deepening democratic engagement, enhancing governance quality, and fostering balanced regional growth. The results indicate that Korea’s case demonstrates how a unitary state can successfully implement decentralization through consistent legal frameworks, responsible leadership, and enduring political will.
Keywords: decentralization; local autonomy; public administration